2000
DOI: 10.1007/s005950070096
|View full text |Cite
|
Sign up to set email alerts
|

Pathomorphological and histological prognostic factors in curatively resected ductal adenocarcinoma of the pancreas

Abstract: The fate of patients with potentially resectable carcinomas is not only determined by the pTNM tumor stage, but also possibly by tumor-biological factors. The aim of this study was to identify these prognostic factors in patients undergoing primary curative (R0) resection. The study retrospectively analyzed 113 patients with ductal adenocarcinoma who were operated on between 1986 and 1995. R0 resection was able to be performed in 93 patients. Lymph node metastases were found in 73%. The rates of lymph vessel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 26 publications
3
37
1
1
Order By: Relevance
“…Poorly differentiated histology (found in approximately one-third of cases), positive resection margins (present in up to 30% of cases) and tumour size greater than 2-3 cm are all associated with worse prognosis. In large surgical series, over 70% of patients in whom curative resection was carried out were found to have malignant invasion of local lymph nodes [8,9]. Even in those patients with negative nodes, invasion of the lymphatic vessels is commonly seen.…”
Section: The Results Of "Curative" Resectionmentioning
confidence: 99%
“…Poorly differentiated histology (found in approximately one-third of cases), positive resection margins (present in up to 30% of cases) and tumour size greater than 2-3 cm are all associated with worse prognosis. In large surgical series, over 70% of patients in whom curative resection was carried out were found to have malignant invasion of local lymph nodes [8,9]. Even in those patients with negative nodes, invasion of the lymphatic vessels is commonly seen.…”
Section: The Results Of "Curative" Resectionmentioning
confidence: 99%
“…8,[30][31][32] Finally, 18 articles were included after reading the full papers (Table 1). 4,[15][16][17][18][19][33][34][35][36][37][38][39][40][41][42][43][44] …”
Section: Search Strategy and Study Identificationmentioning
confidence: 99%
“…Tumor diameter with 3cm and 4 cm cut-offs are not specified in the staging and thus causing conflicts about selection of the tumor size cut-off in defining the tumor stage. Many studies have favored the AJCC tumor staging cut-off of 2 cm, [14][15][16] whereas there are studies [17][18][19] which reports the indication for reconsideration of the tumor stage cut-off, to provide more precise reference for staging and predicting survival outcome. Moreover, the impact of tumor size on survival outcome also remains controversial.…”
mentioning
confidence: 99%
“…Several studies examined the impact of perineural invasion on survival in resected pancreatic adenocarcinoma, reporting infiltration as a significant prognostic variable. In fact perineural invasion was associated with poor survival following pancreaticduodenectomy [9][10][11][12][13]. Again, several studies showed that blood vessel invasion was associated with poor outcome in patients with resected pancreatic cancer [11,14,15].…”
Section: Introductionmentioning
confidence: 99%